Impact of Interventional Radiology in Modern-Day Pancreatic Surgery - Kulkarni, Suyash; Shetty, Nitin S.; Rameswarapu, David Narayan; Gala, Kunal; Shrikhande, Shailesh V.; Choudhary, Vikram; Bhandare, Manish (Journal of Clinical Interventional Radiology ISVIR, 2025)
To evaluate the role of interventional radiology (IR) in modern-day pancreatic surgery.Study design: An audit of prospectively maintained electronic medical records.Duration of study: All patients who required image-guided interventions for postpancreatectomy complications from January 2014 to December 2019 were identified and reviewed.Among 758 patients who underwent pancreatectomy, 206 (27.2%) developed complications. Of these, 46 patients (6%) experienced postpancreatectomy hemorrhage (PPH), with 30 patients (3.96%) requiring intervention; 13 patients (43.3%) underwent angioembolization, of whom 5 (38.46%) died due to causes unrelated to PPH, while 17 patients (56.7%) underwent surgical re-exploration. Although the 90-day mortality rates were not statistically significant, they appeared to be higher in the endovascular group (38.46 vs. 17.6%). Intra-abdominal fluid collections were observed in 173 patients (22.8%), with 147 (85%) undergoing image-guided interventions and 23 (13.3%) undergoing surgical re-exploration. The 90-day mortality rates were 6.12 and 21.7% in the IR and surgical groups, respectively. Biliary complications occurred in 31 patients (4%), of which 18 (58%) underwent image-guided intervention and 11 (35.5%) underwent surgical re-exploration. The 90-day mortality rates were 27.78 and 35.5% in the IR and surgical groups, respectively. Image-guided interventions successfully prevented re-exploration in 61.5% of PPH cases, 88.9% of biliary complications, and 99.3% of intra-abdominal fluid collections.IR procedures are safe and effective, and the synergistic role of the interventional radiologist provides a minimally invasive approach in the management of postpancreatectomy complications while reducing the need for re-exploration, thereby reducing the recovery time and preventing morbidity associated with re-exploration.
Keywords: postpancreatectomy complications; interventional radiology; image-guided interventions